Multifunctional solid@MOF nanohybrids toward surface-enhanced raman spectroscopy (SERS) and electrochemistry applications - Sim, Howard Yi Fan (Nanyang Technological University, 2021)
Solid-MOF nanohybrids are an emerging platform for applications in SERS detection, reaction monitoring and catalysis. However, current applications revolve either gas or liquid-based molecules, which deprive it for real-life multiphase applications. Notably, solid-MOFs have interfacial cavities where molecular interactions take place under the influence of both functional solid nanoparticles and MOFs. In this thesis, we address these challenges by designing multifunctional solid@MOF for SERS and electrochemical applications. In chapter 2, we showcase solid@MOF practicality in driving immiscible gas-liquid biphasic molecules with in-situ monitoring at ambient conditions. In chapter 3, we demonstrate real-time stand-off atmospheric monitoring where we integrate both remote detection and Raman spectroscopy to obtain the molecular fingerprints up to 10 m. In chapter 4 and 5, we exploit ZIF excellent gas sorbing ability and develop various metallic nanocatalyst@ZIF to drive ambient electrochemical nitrogen reduction. Finally, I end my thesis with a research summary and outlook for future work.